Exploring supply chain management practices in the Omani SMEs - Al-Shahri, Ahmed Ali; Mohd Yusuff, Rosnah (2005)
Supply chain management is the area that includes the planning and execution of supply chain that ensures a coordinated flow within the manufacturer and among integrated companies. A typical supply chain includes the inbound flow of goods from suppliers, the manufacture and assembly of sellable products, warehousing and inventory tracking, order entry and order management, distribution across all channels, and delivery to the end customer. This research investigates the extent to which the Omani industries recognize the importance of supply chain management practice in their business process. The recent developments in the international business arena have driven firms all over the world to adopt new strategies for better product quality with low cost to ensure customer satisfaction. Hence, a well-executed supply chain ensures that goal, knowing that major chunk of operation cost is attributed to material handling and flow. Additionally, Oman 2020 vision requires companies to move up to the next level where they will be able to compete on the international stage in order to achieve the promising objective. The research has been conducted using a survey questionnaire, which has been designed to best capture the various factors that contribute to SCM success. Those factors include performance measures, costs, outsourcing, demand management, inventory management, IT utilization, and degree of integration. The results indicate that supply chain management is valued in the business community in Oman and it is seen as an essential factor that contributes significantly to business success. Moreover, the results prove that cost reduction is the prime performance measure used to evaluate SCM success in the surveyed companies. Finally, the results show that integration and IT utilization, which both considered as the backbone of SCM, are almost completely neglected by the respondent organizations.